Laboratory Cultures - Jones-Imhotep, Edward (Scientia Canadensis, 2005)
AbstractThis essay uses the visual and material cultures of two laboratories as a way of initiating an historiographical discussion about what it means to write the history of science and technology in Canada. It uses a potentially familiar topic—the conception and construction of the Alouette satellite—to illustrate how the discipline might shed its self-conscious preoccupation with discoveries and innovations, and instead focus its attention on a revised exploration of the question: what is Canadian about Canadian science and technology?